2008
DOI: 10.1111/j.1742-6723.2008.01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving documentation of endotracheal intubation in an adult emergency department

Abstract: Documentation improved slightly following the intervention, but was still unsatisfactory. We believe that to achieve an adequate level of documentation in the medical record for an episode of intubation, there needs to be a formal and structured mechanism, either via mandatory use of a specifically designed form and/or by participation in an organized data registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…This might be related to inform nurses that documentation protects and safe her from falling in mistakes. This result was in agreement with (Winton et al, 2008) who found in the study about " Improving documentation of endotracheal intubation in an adult emergency department, Emergency medicine Australasia" that the nurses improved documentation of endotracheal tube care after implementing the program.…”
Section: Resultssupporting
confidence: 91%
“…This might be related to inform nurses that documentation protects and safe her from falling in mistakes. This result was in agreement with (Winton et al, 2008) who found in the study about " Improving documentation of endotracheal intubation in an adult emergency department, Emergency medicine Australasia" that the nurses improved documentation of endotracheal tube care after implementing the program.…”
Section: Resultssupporting
confidence: 91%
“…Regular teaching and competency assessments are required to ensure ongoing currency for all clinicians involved in emergent intubations of patients. Ongoing audit of clinical practice should occur and this might include the development of a hospital‐specific form to improve documentation of all intubations …”
Section: Discussionmentioning
confidence: 99%
“…The documentation of emergency intubations in hospital is poor despite the introduction of documentary pro forma and focused education programmes 2. Preanaesthesia assessments in the hospital environment are also often poor3 and small but statistically non-significant improvements have been attained using unified record-keeping documents 4.…”
Section: Introductionmentioning
confidence: 99%